A CLASSROOM ACTION RESEARCH: IMPROVING SPEAKING SKILLS THROUGH INFORMATION GAP ACTIVITIES - M Afrizal (Universitas Syiah Kuala, 2015)
The research was based on a preliminary study on the causes of problems related to the students’ inability to speak English. One of the research objectives is to describe the atmosphere in improving speaking by using activities in the Information Gap Technique (IGT). The researcher and the collaborator worked together in designing the lesson plans, implementing the actions, making observations and reflecting on the results. The subjects of this research study were second semester students from the English Department at Almuslim University. This study was conducted in three cycles following the procedures for action research, namely planning, implementing, observing and reflecting. To collect data, the researcher used instruments of observations, lists, tests and questionnaires. The data obtained was presented in two ways, qualitatively and quantitatively. The findings showed that IGT activities were effective in improving the speaking abilities of the student in class. This can be seen from the improvements after each cycle. This can be seen by the rise in the students’ mean scores in the test results: 58.8 in the first cycle, 68 in the second cycle and 81.3 in the third cycle. Improvement was also seen based on the results from the observations that showed positivity, and good responses from the students. From the questionnaire results, it was found that the mean score for the students’ perception was 3,616. This means that the students responded positively to the implementation of this technique.